Elements of the Theory of Dynamic Networks. - MICHAIL, OTHON; SPIRAKIS, PAUL G. (Communications of the ACM, 2018)
The article discusses dynamic networks. Topics include the consideration of time as an integral element of dynamic networks, and traditional approaches and measures for static and dynamic networks.